Problematika Kebebasan Beragama Di Indonesia Refleksi Kritis Atas Kasus Jemaah Ahmadiyah - Falaurine, Ester (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2011)
The state of Indonesia protects and guarantees the freedom of religion with- out any discrimination to each citizen. Everyone is free to embrace any religion and to do worship according to his or her beliefs. This article de- scribes the religious freedom in this country and highlights its subsequent problems. Is it true that religious freedom goes in accordance with the constitution of the country?, The Ahmadiyah adherents, however, were badly treated in these recent years. Their communities had to undergo expulsion and persecution in many places throughout the country. They were stripped of their human dignity and deprived of their basic rights, and many of them were even murdered. Historically speaking, they have been in Indonesia since the first quarter of the twentieth century. They also belonged to the fighters for the independence of the country (1945). Finally, their existence was yuridically acknowledged by the government in 1953. Our questions, then, are: